Association of lean body mass with cardiometabolic risk factors in healthy postmenopausal women. (11th February 2014) - Peppa, Melpomeni; Koliaki, Chrysi; Boutati, Eleni; Garoflos, Efstathios; Papaefstathiou, Athanasios; Siafakas, Nikolaos; Katsilambros, Nicholas; Raptis, Sotirios A.; Hadjidakis, Dimitrios I.; Dimitriadis, George D.
<x xml:space="preserve">Abstract</x> Objective: Aim of this study was to investigate the association of total and regional lean body mass (LBM) with cardiometabolic risk factors in healthy obese and nonobese postmenopausal women. Methods: A total of 150 postmenopausal women (age 54 ± 7 years, BMI 29.6 ± 5.8 kg/m2) underwent a comprehensive assessment of cardiometabolic risk, including metabolic syndrome (MS). Body composition analysis was performed with Dual‐energy X‐ray Absorptiometry, and multiple height‐adjusted indices of total and regional LBM were evaluated. Results: After controlling for age, diet, physical activity, and total fat mass, most indices of total, central, and peripheral LBM displayed significant positive correlations with cardiometabolic risk factors. Most associations were no longer significant after controlling for waist circumference, with the only exception of lean mass in the arms, which remained significantly associated with the presence and severity of MS (number of MS abnormalities), independently of central adiposity. A significant additive interaction was found between lean mass in the arms and waist circumference in increasing the prevalence of MS. Conclusions: LBM is unfavorably associated with cardiometabolic risk factors in healthy postmenopausal women. Whether LBM, especially in arms, is associated with cardiometabolic health independently of central fat distribution in postmenopausal women, merits further investigation.